Pain threshold correlates with functional scores in osteoarthritis patients - Kuni, Benita; Wang, Haili; Rickert, Markus; Ewerbeck, Volker; Schiltenwolf, Marcus (Acta orthopaedica, 2015)
Background and purpose: Pain sensitization may be one of the reasons for persistent pain after technically successful joint replacement. We analyzed how pain sensitization, as measured by quantitative sensory testing, relates preoperatively to joint function in patients with osteoarthritis (OA) scheduled for joint replacement. Patients and methods: We included 50 patients with knee OA and 49 with hip OA who were scheduled for joint replacement, and 15 control participants. Hip/knee scores, thermal and pressure detection, and pain thresholds were examined. Results: Median pressure pain thresholds were lower in patients than in control subjects: 4.0 (range: 0-10) vs. 7.8 (4-10) (p = 0.003) for the affected knee; 4.5 (2-10) vs. 6.8 (4-10) (p = 0.03) for the affected hip. Lower pressure pain threshold values were found at the affected joint in 26 of the 50 patients with knee OA and in 17 of the 49 patients with hip OA. The American Knee Society score 1 and 2, the Oxford knee score, and functional questionnaire of Hannover for osteoarthritis score correlated with the pressure pain thresholds in patients with knee OA. Also, Harris hip score and the functional questionnaire of Hannover for osteoarthritis score correlated with the cold detection threshold in patients with hip OA. Interpretation: Quantitative sensory testing appeared to identify patients with sensory changes indicative of mechanisms of central sensitization. These patients may require additional pain treatment in order to profit fully from surgery. There were correlations between the clinical scores and the level of sensitization.
Gesehen am 10.04.2017